Safegaurding the right to freedom from torture in Africa : the Robben Island Guidelines - Sloth-Nielsen, Julia (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2005.